Water-resistant sealing layer for sealing microcells of electro-optical devices - Patent Application 20070123633
A sealing layer made from a combination of polyurethane and poly(vinyl alcohol) with acetoacetate functional groups addresses the challenges of fluid barrier and water resistance in microcells, ensuring effective sealing and electro-optic performance.
Patent Information
- Application Number
- JP2024549174
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-08
- Filing Date
- 2023-04-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-06
AI Technical Summary
Existing sealing layers for microcells in electro-optical devices face challenges in providing effective barriers against non-polar fluids and water resistance, which can lead to fluid diffusion and sagging of the sealing layer.
A sealing layer composed of a combination of polyurethane and poly(vinyl alcohol), where the poly(vinyl alcohol) contains acetoacetate functional groups, is used. This combination provides good barrier properties against non-polar fluids and water resistance, while maintaining electro-optic performance.
The proposed sealing layer effectively prevents fluid diffusion from microcells, maintains structural integrity under water exposure, and does not adversely affect the electro-optic performance of the device.
Smart Images

Figure 2025507425000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 63 / 329,066, filed April 8, 2022, which is incorporated by reference in its entirety along with all other patents and patent applications disclosed herein.
[0002] FIELD OF THEINVENTION The present invention relates to an encapsulation layer for sealing microcells of an electro-optical device. The encapsulation layer comprises a combination of polyurethane and poly(vinyl alcohol), the poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure. The encapsulation layer is water resistant and exhibits good barrier properties to non-polar fluids. [Background technology]
[0003] 2. Background of the Invention The term "electro-optic" as applied to a material or display is used herein in its conventional sense in the imaging arts to refer to a material having first and second display states differing in at least one optical property, said material changing from its first display state to its second display state by application of an electric field to said material. The optical property is typically color perceptible to the human eye, but may be another optical property, for example light transmission, reflectance, emission, or, in the case of displays intended to be machine-readable, pseudocolor in the sense of a change in reflectance of electromagnetic wavelengths outside the visible range.
[0004] The terms "bistable" and "bistable" are used herein in their conventional sense in the art to refer to displays that include display elements having first and second display states that differ in at least one optical property, such that after any given element is driven by an addressing pulse of finite duration to assume either its first or second display state, that state persists after the addressing pulse is terminated for at least several times, e.g., at least four times, the minimum duration of the addressing pulse required to change the state of the display element. U.S. Pat. No. 7,170,670 shows that some particle-based electrophoretic displays capable of gray scale are stable not only in their extreme black and white states but also in intermediate gray states, and the same is true for several other types of electro-optical devices. Displays of this type are more appropriately referred to as "multistable" rather than bistable, although for convenience the term "bistable" may be used herein to encompass both bistable and multistable displays.
[0005] One type of electro-optical device that has been the subject of active research and development for several years is the particle-based electrophoretic display, in which a plurality of electrically charged particles move through a fluid under the influence of an electric field. Electrophoretic displays can have attributes of good brightness and contrast, wide viewing angles, state bistability, and low power consumption when compared to liquid crystal displays.
[0006] Numerous patents and applications assigned to or in the name of Massachusetts Institute of Technology (MIT), E Ink Corporation, E Ink California, LLC, and affiliates describe various techniques used for encapsulation and microcell electrophoretic media and other electro-optic media. Encapsulated electrophoretic media includes a number of small capsules, each of which itself includes an internal phase containing electrophoretically mobile particles in a fluid medium, and a capsule wall surrounding the internal phase. Typically, the capsules are themselves held within a polymeric binder to form a coherent layer located between two electrodes. In microcell electrophoretic displays, the charged particles and fluid are not encapsulated within microcapsules, but instead are held within a number of cavities formed within a carrier medium, typically a polymeric film.
[0007] The techniques described in these patents and applications include:
[0008] (a) Electrophoretic particles, fluids, and fluid additives (see, e.g., U.S. Pat. Nos. 7,002,728 and 7,679,814)
[0009] (b) Capsules, binders, and encapsulation processes (see, e.g., U.S. Pat. Nos. 6,922,276 and 7,411,719)
[0010] (c) Microcell structures, wall materials, and methods of forming the microcells (see, e.g., U.S. Pat. Nos. 7,072,095 and 9,279,906).
[0011] (d) Methods for filling and sealing microcells (see, e.g., U.S. Pat. Nos. 7,144,942, 7,005,468, and 7,715,088, and U.S. Patent Application Publication Nos. 2004-0120024, 2004-0219306, 2022-0244612, and 2022-0251364).
[0012] (e) Films and subassemblies containing electro-optical materials (see, e.g., U.S. Pat. Nos. 6,982,178 and 7,839,564)
[0013] (f) Backplanes, adhesive layers, and other auxiliary layers and methods used in displays (see, e.g., U.S. Pat. Nos. 7,116,318 and 7,535,624)
[0014] (g) Color formation and color control (see, e.g., U.S. Pat. Nos. 7,075,502 and 7,839,564)
[0015] (h) Methods for driving displays (see, e.g., U.S. Pat. Nos. 7,012,600 and 7,453,445)
[0016] (i) display applications (see, e.g., U.S. Pat. Nos. 7,312,784 and 8,009,348); and
[0017] (j) Non-electrophoretic displays (as described in U.S. Pat. No. 6,241,921 and U.S. Patent Application Publication No. 2015 / 0277160), as well as non-display applications of encapsulation and microcell technology (see, e.g., U.S. Pat. No. 7,615,325, and U.S. Patent Application Publication Nos. 2015 / 0005720 and 2016 / 0012710).
[0018] The contents of all of the above references are incorporated herein by reference in their entirety.
[0019] Structures with a plurality of sealed microcells containing a dispersion of charged pigment particles in a non-polar fluid are commercially used in electro-optical devices. Microcells are also known in the literature as microcavities or microcups. A typical process for making sealed microcell structures for electro-optical devices includes (a) fabricating a polymer sheet with a plurality of microcavities by microembossing, each microcavity having an opening, (b) filling the microcavities with an electrophoretic medium, which is a dispersion of charged pigment particles in a non-polar fluid, and (c) sealing the microcavities with a sealing composition to form a sealing layer. The sealed microcavities containing the electrophoretic medium form the electro-optical material layer of the device. The electro-optical material layer is disposed between a front electrode and a rear electrode. Application of an electric field across the electrophoretic medium via these electrodes causes the pigment particles to migrate through the electrophoretic medium to create an image. The sealing layer plays an important role in the function and performance of the device.
[0020] First, because the sealing layer contacts the electrophoretic medium and seals it within the microcavity, (1) the sealing layer must be practically insoluble in the non-polar fluid of the electrophoretic medium, and (2) the sealing layer must be a good barrier to the non-polar fluid so that the non-polar fluid does not diffuse out of the microcell during the lifetime of the device. Poor barrier properties of the sealing layer to the non-polar fluid will lead to loss of fluid from the electrophoretic medium and sagging of the sealing layer.
[0021] Second, in certain applications where the electrophoretic device may be subjected to harsh conditions, such as exposure to water or even immersion in water, the sealing layer needs to be water resistant, i.e., it must be resilient in water and protect the electrophoretic medium under such conditions. The technical task of providing a sealing composition that forms a sealing layer with all these characteristics is difficult because different objectives may require different formulation strategies. For example, barrier properties against non-polar fluids typically require more hydrophilic components of the sealing layer, whereas such components are more sensitive to water. Thus, there is a need for a sealing composition that forms a sealing layer that is optimized for improved barrier against non-polar fluids and improved water resistance. The inventors of the present invention have found that a sealing layer formed by an aqueous sealing composition that includes a combination of polyurethane and poly(vinyl alcohol), where the poly(vinyl alcohol) contains acetoacetate functional groups in its molecular structure, has good water resistance and good barrier properties against non-polar fluids, as well as good electro-optical performance. [Prior art documents] [Patent documents]
[0022] [Patent Document 1] U.S. Patent No. 7,002,728 [Patent Document 2] U.S. Patent No. 7,679,814 [Patent Document 3] U.S. Patent No. 6,922,276 [Patent Document 4] U.S. Patent No. 7,411,719 [Patent Document 5] U.S. Patent No. 7,072,095 [Patent Document 6] U.S. Patent No. 9,279,906 [Patent Document 7] U.S. Patent No. 7,144,942 [Patent Document 8] U.S. Patent No. 7,005,468 [Patent Document 9] U.S. Patent No. 7,715,088 [Patent Document 10] US Patent Application Publication No. 2004 / 0120024 [Patent Document 11] US Patent Application Publication No. 2004 / 0219306 [Patent Document 12] U.S. Patent Application Publication No. 2022 / 0244612 [Patent Document 13] U.S. Patent Application Publication No. 2022 / 0251364 [Patent Document 14] U.S. Patent No. 6,982,178 [Patent Document 15] U.S. Patent No. 7,839,564 [Patent Document 16] U.S. Patent No. 7,116,318 [Patent Document 17] U.S. Patent No. 7,535,624 [Patent Document 18] U.S. Patent No. 7,075,502 [Patent Document 19] U.S. Patent No. 7,012,600 [Patent Document 20] U.S. Patent No. 7,453,445 [Patent Document 21] U.S. Patent No. 7,312,784 [Patent Document 22] U.S. Patent No. 8,009,348 [Patent Document 23] U.S. Patent No. 6,241,921 [Patent Document 24] US Patent Application Publication No. 2015 / 0277160 [Patent Document 25] U.S. Patent No. 7,615,325 [Patent Document 26] US Patent Application Publication No. 2015 / 0005720 [Patent Document 27] US Patent Application Publication No. 2016 / 0012710 Summary of the Invention [Means for solving the problem]
[0023] Summary of the Invention In one aspect, the present invention relates to a sealing layer comprising: (i) 40 to 95 weight percent poly(vinyl alcohol), based on the weight of the sealing layer excluding solvent, the poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure; and (ii) 5 to 60 weight percent polyurethane, based on the weight of the sealing layer excluding solvent. The polyurethane of the sealing layer may have a peak melting temperature of 115° C. and higher, and a crystallinity index of 8% and higher. The polyurethane of the sealing layer may be an ester polyurethane, an ether polyurethane, or a polycarbonate polyurethane. The polyurethane may have a number average molecular weight of 1,000 to 2,000,000 Daltons. The polyurethane of the sealing layer may be crosslinked. The polyurethane crosslinker may be a polyisocyanate, a polyfunctional polycarbodiimide, a polyfunctional aziridine, a silane coupling agent, a boron / titanium / zirconium based crosslinker, or a melamine formaldehyde. The poly(vinyl alcohol) of the sealing layer may be crosslinked. The poly(vinyl alcohol) of the sealing layer may have a number average molecular weight of 1,000 to 1,000,000 Daltons. The poly(vinyl alcohol) may have a degree of hydrolysis of 90 to 99 percent. The poly(vinyl alcohol) may be crosslinked. The crosslinked poly(vinyl alcohol) may be formed by reaction of the poly(vinyl alcohol) with a crosslinking agent, the crosslinking agent being selected from the group consisting of dialdehydes and organozirconates. The crosslinking agent for the poly(vinyl alcohol) may be selected from the group consisting of glyoxal, ZrO(OH)Cl*nH2O, and (NH4)2ZrO(CO3)2. Both the polyurethane and the poly(vinyl alcohol) of the sealing layer may be crosslinked. The poly(vinyl alcohol) of the sealing layer may be non-crosslinked. The sealing layer may include a surfactant. The surfactant of the sealing layer may be an acetylenic diol or an organosilicone surface tension reducing agent.
[0024] The sealing layer may be formed by an aqueous sealing composition. The aqueous sealing composition may include: (ii) 40 to 95 weight percent poly(vinyl alcohol), based on the weight of the aqueous sealing composition excluding the solvent, the poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure; and (iii) an aqueous carrier; and (ii) 5 to 60 weight percent polyurethane, based on the weight of the aqueous sealing composition excluding the solvent; and (iii) an aqueous carrier. The polyurethane of the aqueous sealing composition may be an ester polyurethane, an ether polyurethane, or a carbonate polyurethane. The polyurethane of the aqueous sealing composition may have a peak melting temperature of 115° C. and higher, and a crystallinity index of 8% and higher. The polyurethane may have a number average molecular weight of 1,000 to 2,000,000 Daltons. The aqueous sealing composition may further include a polyurethane crosslinker. The polyurethane crosslinker may be a polyisocyanate, a polyfunctional polycarbodiimide, a polyfunctional aziridine, a silane coupling agent, a boron / titanium / zirconium based crosslinker, or a melamine formaldehyde. The aqueous sealing composition may be free of a poly(vinyl alcohol) crosslinker. The aqueous sealing composition may include a poly(vinyl alcohol) crosslinker. The aqueous sealing composition including a poly(vinyl alcohol) crosslinker may have a pot life of greater than 1 day, greater than 3 days, greater than 5 days, or greater than 7 days. The poly(vinyl alcohol) of the aqueous sealing composition may have a number average molecular weight of 1,000 to 1,000,000 Daltons. The poly(vinyl alcohol) may have a degree of hydrolysis of 90 to 99 percent. The aqueous sealing composition may include both a polyurethane crosslinker and a poly(vinyl alcohol) crosslinker. The sealing layer may include a surfactant. The surfactant of the sealing layer may be an acetylenic diol or an organosilicone surface tension reducing agent. The aqueous sealing composition may include a polymeric rheology modifier. The polymeric rheology modifier may be a hydrophobically modified alkali swellable acrylic emulsion.
[0025] The sealing layer may be used to seal the microcells of an electrophoretic display. The electrophoretic display may include, in order, a first light-transmissive electrode layer, an electro-optical material layer, and a second electrode layer. The electro-optical material layer includes a sealing layer and a microcell layer. The microcell layer includes a plurality of microcells, each of the plurality of microcells including a bottom, a wall, and an opening, each of the plurality of microcells containing an electrophoretic medium. The electrophoretic medium includes at least one type of charged pigment particles dispersed in a non-polar fluid. The electrophoretic fluid may include two or more types of charged pigment particles. The electrophoretic medium may include four types of charged pigment particles, and the colors of the four or more types of pigment particles are selected from the group consisting of white, magenta, yellow, cyan, blue, red, green, and black. The sealing layer spans the openings of the plurality of microcells. The sealing layer may be disposed between the microcell layer and the second electrode layer. The sealing layer may be disposed between the microcell layer and the first light-transmissive electrode layer. The sealing layer comprises: (i) 40 to 95 weight percent poly(vinyl alcohol), based on the weight of the sealing layer excluding solvent, the poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure; and (ii) 5 to 60 weight percent polyurethane, based on the weight of the sealing layer excluding solvent. The electrophoretic display may further comprise a piezoelectric material layer, where stress on the layer of piezoelectric material produces an optical change in the electro-optic material layer. The piezoelectric material layer may be located (a) between the electro-optic material layer and the first light-transmissive electrode layer, or (b) between the electro-optic material layer and the second electrode layer.
[0026] The sealing layer may also be used to seal the microcells of the front plane laminate. The front plane laminate may include a first light-transmitting electrode layer, an electro-optic material layer, an adhesive layer, and a release sheet. The electro-optic material layer is disposed between the first light-transmitting electrode layer and the second electrode layer. The electro-optic material layer includes a plurality of microcells and a sealing layer.
[0027] The sealing layer may also be used to seal the microcells of the front plane laminate. The front plane laminate may include a first light-transmitting electrode layer, an electro-optic material layer, an adhesive layer, and a release sheet. The electro-optic material layer is disposed between the first light-transmitting electrode layer and the second electrode layer. The electro-optic material layer includes a plurality of microcells and a sealing layer. The sealing layer may be formed by an aqueous sealing composition. Each of the plurality of microcells includes a bottom, a wall, and an opening, and each of the plurality of microcells contains an electrophoretic medium, the electrophoretic medium including at least one type of electrically charged pigment particles dispersed in a non-polar fluid. The sealing layer spans the openings of the plurality of microcells. The front plane laminate may further include a piezoelectric material layer, where stress on the layer of piezoelectric material causes an optical change in the electro-optic material layer. The piezoelectric material layer may be located (a) between the electro-optic material layer and the first light-transmitting electrode layer, (b) between the electro-optic material layer and the adhesive layer, or (c) next to and in line with the electro-optic material layer.
[0028] The sealing layer may also be used to seal the microcells of the double release sheet. The double release sheet may include a first release sheet, a first adhesive layer, an electro-optic material layer, a second adhesive layer, and a second release sheet. The electro-optic material layer may include a plurality of microcells and a sealing layer. The sealing layer may be formed from an aqueous sealing composition. Each of the plurality of microcells includes a bottom, a wall, and an opening, and each of the plurality of microcells contains an electrophoretic medium, the electrophoretic medium including at least one type of electrically charged pigment particles dispersed in a non-polar fluid. The sealing layer spans the openings of the plurality of microcells. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 shows the structure of multiple microcells before they are filled and sealed.
[0030] [Diagram 2] FIG. 2 shows an example of an electro-optical device that includes a microcell structure.
[0031] [Diagram 3] FIG. 3 illustrates one example of a front plane laminate assembly that can be used to form an electro-optical device that includes a microcell structure.
[0032] [Figure 4] FIG. 4 shows an example of a double release sheet that can be used to form an electro-optic device containing a microcell structure.
[0033] [Diagram 5] Figure 5 shows a method for fabricating a microcell using a roll-to-roll process.
[0034] [Figure 6AB] 6A and 6B detail the creation of a microcell using photolithographic exposure through a photomask of a conductor film coated with a thermosetting precursor.
[0035] [Figure 6C-D] Figures 6C and 6D detail an alternative embodiment fabricated using photolithography, in which a combination of top and bottom exposure is used, allowing one lateral wall to be hardened with a top photomask exposure and another lateral wall to be hardened with a bottom exposure through a non-transparent base conductor film.
[0036] [Figure 7AB] 7A-7D show the steps of filling and sealing the array of microcells. [Figure 7C-D] 7A-7D show the steps of filling and sealing the array of microcells.
[0037] [Figure 8] 8-13 show side views of electro-optic displays of the present invention, said displays including a layer of piezoelectric material. [Figure 9] 8-13 show side views of electro-optic displays of the present invention, said displays including a layer of piezoelectric material. [Figure 10] 8-13 show side views of electro-optic displays of the present invention, said displays including a layer of piezoelectric material. [Figure 11] 8-13 show side views of electro-optic displays of the present invention, said displays including a layer of piezoelectric material. [Figure 12] 8-13 show side views of electro-optic displays of the present invention, said displays including a layer of piezoelectric material. [Figure 13] 8-13 show side views of electro-optic displays of the present invention, said displays including a layer of piezoelectric material.
[0038] [Figure 14] 14A and 14B show examples of aqueous sealing compositions and the structures of electro-optical devices used to evaluate the corresponding sealing layers.
[0039] [Figure 15] 15A and 15B show microscopic images of the microcells evaluated for barrier properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] Detailed Description of the Invention The term "excluding solvent" when referring to the weight of the sealing layer of the present invention means that the weight of the sealing layer referred to does not include water and other solvents that may be present in the sealing layer.
[0041] As used herein, the term "molecular weight" or "MW" refers to number average molecular weight, unless otherwise indicated. Number average molecular weight can be measured by gel permeation chromatography.
[0042] The terms "crosslinking agent" and "crosslinker" are synonymous and refer to an agent that can react with a crosslinkable polymer to form a crosslinked polymer.
[0043] The term "pot life" of a composition is the amount of time that the composition remains in a workable liquid form at a particular temperature.
[0044] The degree of hydrolysis of polyvinyl alcohol homopolymers and copolymers is conventionally reported by the manufacturers of such polymers and indicates the ratio (moles) of vinyl alcohol units to the total vinyl units in the polymer, other units including vinyl acetate (esters) or other units.
[0045] "Water-resistant sealing layer" refers to the integrity of the sealing layer of an electro-optic display after immersion of the device in water of a particular pH and temperature for a particular period of time.
[0046] The term "light transmissive" is used herein to mean that a layer so designated transmits sufficient light to enable an observer looking through that layer to observe a change in the display state of the electrophoretic medium, which will normally be viewed through the light transmissive electrode layer, if present, and the adjacent substrate, and where the electrophoretic medium exhibits changes in reflectance at non-visible wavelengths, the term "light transmissive" should of course be interpreted to refer to the transmission of the relevant non-visible wavelengths.
[0047] The term "contrast ratio" (CR) of an electro-optic display is defined as the ratio of the luminance of the brightest color (white) to the luminance of the darkest color (black) that the display can produce. A high contrast ratio or CR is usually a desirable aspect of a display.
[0048] Piezoelectricity is an electrical charge that accumulates in solid materials in response to applied mechanical stress. Suitable piezoelectric materials include polyvinylidene fluoride (PVDF), quartz (SiO2), berlinite (AlPO4), gallium orthophosphate (GaPO4), tourmaline, barium titanate (BaTiO3), lead zirconate titanate (PZT), zinc oxide (ZnO), aluminum nitride (AlN), lithium tantalate, lanthanum gallium silicate, sodium potassium tartrate, and any other known piezoelectric material. Piezoelectricity can be used to drive the pigments of the electrophoretic material of an electro-optic display and generate electrical charges to power the electro-optic display. An electro-optic display can be powered only by the electrical charge generated by the piezoelectric material and can operate without a power source. For example, in the case of an electro-optic display having an electrophoretic material, a voltage can be generated by bending or introducing stress into the piezoelectric material, and this voltage can be used to move the color pigments of the electrophoretic material of the electro-optic display. Electro-optic displays comprising an electrophoretic medium and piezoelectric materials have been previously disclosed, for example, in US Pat. Nos. 7,002,728 and 7,679,814.
[0049] A. Microcell Structure
[0050] 1 shows the structure of a number of microcells 100 before being filled and sealed. Each microcell includes a base 101, a wall 102, and an opening 103.
[0051] B. Structure of an electro-optical device including a microcell structure
[0052] FIG. 2 shows an example of an electro-optical device 200 including a plurality of microcells and a sealing layer according to the present invention. This example of the electro-optical device 200 includes a first light-transmissive electrode layer 210, a microcell layer 220, a sealing layer 230, an adhesive layer 240, and a second electrode layer 250. The microcell layer 220 includes a plurality of microcells defined by a bottom 101 and a wall 102. Each of the plurality of microcells has an opening 103. Each of the plurality of microcells contains an electrophoretic medium 225, the electrophoretic medium 225 including electrically charged particles in a non-polar fluid. The microcells are sealed with a sealing layer 230, which spans the openings 103 of the plurality of microcells. The second electrode layer 250 is connected to the sealing layer 230 with an adhesive layer 240. The electro-optical material layer 260 of the electro-optical device 200 includes the microcell layer 220 and the sealing layer 230. A source of electric field (not shown in FIG. 2) may connect the first light-transmissive electrode layer 210 with the second electrode layer 250. Application of an electric field across the electrophoretic material layer causes charged particles to move through the electrophoretic medium, creating an image that may be viewed by an observer looking from the viewing side 205 of the electro-optic device 200. An optional primer layer (not shown in FIG. 2) may be disposed between the first light-transmissive electrode layer 210 and the plurality of microcells. The sealing layer is water resistant and comprises 40 to 95 weight percent poly(vinyl alcohol), based on the weight of the sealing layer excluding solvent, where the poly(vinyl alcohol) contains acetoacetate functional groups in its molecular structure; and 5 to 60 weight percent polyurethane, based on the weight of the sealing layer excluding solvent.
[0053] The example electro-optic device shown in FIG. 2 may be constructed by a front plane laminate 300 shown in FIG. 3. The front plane laminate 300 includes a first light-transmitting electrode layer 210, a microcell layer 220 having a plurality of microcells, a sealing layer 230, an adhesive layer 240, and a release sheet 360. Each of the plurality of microcells contains an electrophoretic medium 225, which includes charged particles in a non-polar fluid. The microcells are sealed with a sealing layer 230, which spans the openings of the plurality of microcells. The release sheet 360 is connected to the sealing layer 230 by an adhesive layer 240. The electro-optic material layer 260 includes the microcell layer 220 and the sealing layer 230. Removal of the release sheet 360 exposes a surface of the adhesive layer 240, which can be connected onto a second electrode layer to form an electro-optic device. An optional primer layer (not shown in FIG. 3) may be disposed between the first light transmissive electrode layer 210 and the microcell layer 220 .
[0054] The example electro-optic device shown in FIG. 2 can also be constructed with a double release sheet 400 shown in FIG. 4. The double release sheet 400 includes a first release sheet 480, a first adhesive layer 470, a microcell layer 220, a sealing layer 230, a second adhesive layer 240, and a second release sheet 360. Each of the plurality of microcells contains an electrophoretic medium 225, which includes charged particles in a non-polar fluid. The microcells are sealed with a sealing layer 230, which spans the openings of the plurality of microcells. The electro-optic material layer 260 includes the microcell layer 220 and the sealing layer 230. The first release sheet 480 is connected to the microcell layer 220 with a first adhesive layer 470. The second release sheet 360 is connected to the sealing layer 230 with a second adhesive layer 240. Removal of the first release sheet 480 exposes a surface of the first adhesive layer 470 that can be connected onto the first light-transmissive electrode layer. Removal of the second release sheet 360 exposes a surface of the second adhesive layer 240 that can be connected onto the second electrode layer to form an electro-optical device. An optional primer layer (not shown in FIG. 4) may be disposed between the first adhesive layer 470 and the microcell layer 220. The sealing layers of the front plane laminate 300 of FIG. 3 and the double release sheet 400 of FIG. 400 are water resistant. They include 40-95 weight percent poly(vinyl alcohol), based on the weight of the sealing layer excluding solvent, where the poly(vinyl alcohol) contains acetoacetate functional groups in its molecular structure; and 5-60 weight percent polyurethane, based on the weight of the sealing layer excluding solvent.
[0055] C. Formation of Microcell Structure
[0056] Techniques for constructing microcells. Microcells can be formed in either a batch process or a continuous roll-to-roll process, as disclosed in U.S. Pat. No. 6,933,098. The latter provides a continuous, low-cost, high-throughput manufacturing technique for generating compartments for use in a variety of applications, including beneficial agent delivery and electrophoretic displays. Microcell arrays suitable for use in the present invention can be created by microembossing, as shown in FIG. 5. The male mold (500) can be placed either above the web 504 or below the web 504 (not shown), although alternative arrangements are possible. See, for example, U.S. Pat. No. 7,715,088, which is incorporated herein by reference in its entirety. The conductive substrate may be constructed by forming a conductor film 501 on a polymer substrate that will be the backing layer of the device. A composition 502 comprising a thermoplastic, a thermoset, or a precursor thereof is then coated onto the conductor film. The thermoplastic or thermosetting precursor layer is embossed by a male mold in the form of a roller, plate, or belt at a temperature above the glass transition temperature of the thermoplastic or thermosetting precursor layer.
[0057] The thermoplastic or thermosetting precursors for preparing the microcells can be multifunctional acrylates or methacrylates, vinyl ethers, epoxides, and their oligomers or polymers, and the like. The combination of multifunctional epoxides and multifunctional acrylates is also very useful to achieve the desired physico-mechanical properties. Crosslinkable oligomers that impart flexibility, such as urethane acrylates or polyester acrylates, may be added to improve the flex resistance of the embossed microcells. The composition may contain polymers, oligomers, monomers, and additives, or it may contain only oligomers, monomers, and additives. The glass transition temperature (or T g ) is typically in the range of about -70°C to about 150°C, or about -20°C to about 50°C. The microembossing process typically gThe microembossing temperature and pressure may be controlled using a heated male mold, or a heated receiving substrate against which the male mold is pressed.
[0058] As shown in FIG. 5, the mold is removed during or after the precursor layer is cured to reveal an array of microcells 503. Curing of the precursor layer can be achieved by cooling, solvent evaporation, crosslinking by radiation, heat, or moisture. If the curing of the thermosetting precursor is achieved by UV radiation, the UV may be irradiated onto the transparent conductor film from the bottom or top of the web, as shown in the two figures. Alternatively, a UV lamp may be placed in the mold. In this case, the mold must be transparent to allow the UV light to be irradiated onto the thermosetting precursor layer through the pre-patterned male mold. The male mold may be prepared by any suitable method, for example, a diamond turning process or a photoresist process followed by etching or electroplating. A master template for the male mold may be fabricated by any suitable method, for example, electroplating. In electroplating, a glass base is sputtered with a thin layer (typically 3000 Å) of seed metal, for example chrome Inconel. The mold is then coated with a photoresist layer and exposed to UV. A mask is placed between the UV and the photoresist layer. The exposed areas of the photoresist are hardened. The unexposed areas are then removed by washing them with a suitable solvent. The remaining hardened photoresist is dried and re-sputtered with a thin layer of seed metal. The master is then ready for electroforming. A typical material used for electroforming is nickel cobalt. Alternatively, the master can be made of nickel by electroforming or electroless nickel deposition. The floor of the mold is typically about 50-400 microns. The master can be made using other microengineering techniques including e-beam writing, dry etching, chemical etching, laser writing, or laser interference, as described in "Replication techniques for micro-optics", SPIE Proc. Vol.3099, pp. 76-82 (1997). Alternatively, the mold can be made by photomachining using plastics, ceramics, or metals.
[0059] Prior to application of the UV curable resin composition, the mold may be treated with a mold release agent that aids in the mold release process. The UV curable resin may be degassed before dispensing and may contain a solvent if necessary. The solvent, if present, evaporates easily. The UV curable resin is dispensed onto the male mold by any suitable means, such as coating, dipping, pouring, or the like. The dispenser may be mobile or stationary. The conductor film is covered with the UV curable resin. If necessary, pressure may be applied to ensure a suitable bond between the resin and the plastic and to control the thickness of the floor of the microcell. Pressure may be applied using laminating rollers, vacuum forming, pressing devices, or any other similar means. If the male mold is metallic and non-transparent, the plastic substrate is typically transparent to the actinic radiation used to cure the resin. Conversely, the male mold may be transparent and the plastic substrate non-transparent to actinic radiation. To obtain good transfer of the molded features onto the transfer sheet, the conductor film needs to have good adhesion with the UV curable resin, and the UV curable resin should have good release properties with respect to the mold surface.
[0060] The microcell array of the present invention typically includes a preformed conductor film, such as indium tin oxide (ITO) conductor lines, although other conductive materials, such as silver or aluminum, may be used. The conductive layer may be backed by or integrated into a substrate (e.g., polyethylene terephthalate, polyethylene naphthalate, polyaramid, polyimide, polycycloolefin, polysulfone, epoxy, and composites thereof). The conductor film may be coated with a radiation-curable polymer precursor layer. The film and precursor layer are then imagewise exposed to radiation to form the microcell wall structure. After exposure, the precursor material is removed from the unexposed areas, leaving the cured microcell walls bonded to the conductor film / support web. Imagewise exposure may be accomplished with UV or other forms of radiation through a photomask to generate an image or predetermined pattern of exposure of the radiation-curable material coated on the conductor film. Although not generally required, the mask may be positioned and aligned with the conductor film, i.e., the ITO lines, so that the transmissive mask portions align with the spaces between the ITO lines and the non-transmissive mask portions align with the ITO material (intended for the microcell floor areas).
[0061] Photolithography. Microcells can be produced using photolithography. A photolithography process for fabricating a microcell array is shown in Figures 6A and 6B. As shown in Figures 6A and 6B, a microcell array 600 may be prepared by exposing a radiation curable material 601a, coated in a known manner on a conductor film 602, to UV light (or alternatively other forms of radiation, electron beam, and the like) through a mask 606 to form walls 102 corresponding to an image projected through the mask 606. The base conductor film 602 is preferably mounted on a supporting substrate base web (603), which may comprise a plastic material.
[0062] In the photomask 606 of Figure 6A, the dark squares 604 represent non-transparent areas and the spaces between the dark squares represent transparent areas 605 of the mask 606. UV is projected through the transparent areas 605 onto the radiation curable material 601a. The exposure is preferably made directly onto the radiation curable material 601a, i.e., the UV does not pass through either the substrate 603 or the base conductor film 602 (top exposure). For this reason, neither the substrate 603 nor the conductor film 602 need to be transparent to the wavelengths of UV or other radiation used.
[0063] As shown in FIG. 6B, the exposed areas, e.g., walls 102, are cured. The unexposed areas (those protected by the non-transparent areas 604 of the mask 606) are then removed by a suitable solvent or developer to form the microcells 607. The solvent or developer is selected from those commonly used to dissolve or reduce the viscosity of radiation curable materials, e.g., methyl ethyl ketone (MEK), toluene, acetone, isopropanol, or the like. Preparation of the microcells can be similarly accomplished by placing a photomask under the conductor film / substrate support web. In this case, UV light is irradiated from the bottom through the photomask, and the substrate needs to be transparent to the radiation.
[0064] Image-wise exposure. Yet another alternative method for preparing the microcell array of the present invention by image-wise exposure is shown in Figures 6C and 6D. When non-transparent conductor lines are used, the conductor lines can be used as a photomask for exposure from the bottom. An additional exposure from the top through a second photomask with non-transparent lines perpendicular to the conductor lines forms durable microcell walls. Figure 6C illustrates the use of both top and bottom exposure principles to produce a microcell array 610 of the present invention. The base conductor film 612 is non-transparent and patterned in lines. The radiation curable material 611a coated on the base conductor film 612 and substrate 603 is exposed from the bottom through the conductor line pattern of 612, which serves as the first photomask. A second exposure is made from the "top" side through a second photomask 616 with a line pattern perpendicular to the conductor lines of 612. The spaces 615 between the lines 614 are substantially transparent to UV light. In this process, the wall material 611a is cured from the bottom up in one horizontal direction and from the top down in the vertical direction, joining to form the walls 102 of the integral microcell 607. The unexposed areas are then removed with a solvent or developer as described above to reveal the microcell 607, as shown in Figure 6D.
[0065] The microcells may be constructed from thermoplastic elastomers, which have good compatibility with the microcells and do not interact with the medium. Examples of useful thermoplastic elastomers include diblock, triblock, and multiblock copolymers of the ABA and (AB)n type, where A is styrene, α-methylstyrene, ethylene, propylene, or norbornene; B is butadiene, isoprene, ethylene, propylene, butylene, dimethylsiloxane, or propylene sulfide; A and B cannot be the same in the formula. The number n is ≧1, preferably 1-10. Particularly useful are diblock or triblock copolymers of styrene or ox-methylstyrene, such as SB (poly(styrene-b-butadiene)), SBS (poly(styrene-b-butadiene-b-styrene)), SIS (poly(styrene-b-isoprene-b-styrene)), SEBS (poly(styrene-b-ethylene / butylene-b-styrene)), poly(styrene-b-dimethylsiloxane-b-styrene), poly(α-methylstyrene-b-isoprene), poly(α-ene-b-isoprene-b-α-methylstyrene), poly(α-methylstyrene-b-propylene sulfide-b-α-methylstyrene), poly(α-methylstyrene-b-dimethylsiloxane-b-α-methylstyrene). Commercially available styrene block copolymers, such as the Kraton D and G series from Kraton Polymer, Houston, Tex., are particularly useful. Crystalline rubbers such as poly(ethylene-co-propylene-co-5-methylene-2-norbornene), or EPDM (ethylene-propylene-diene terpolymer) rubbers, such as Vistalon 6505 (manufactured by Exxon Mobil, Houston, Tex.), and graft copolymers thereof have also been found to be very useful.
[0066] The thermoplastic elastomer may be dissolved in a solvent or solvent mixture that is immiscible with the carrier in the microcell and exhibits a specific gravity less than that of the carrier. Solvents with low surface tension are preferred for the overcoating composition due to their good wetting of the microcell walls and fluids. Solvents or solvent mixtures with a surface tension less than 35 dynes / cm, or less than 30 dynes / cm, are preferred. Suitable solvents include alkanes (preferably C 6~12 Alkanes, such as heptane, octane, or Isopar solvents from Exxon Chemical Company, nonane, decane, and their isomers), cycloalkanes (preferably C 6~12 Cycloalkanes, such as cyclohexane and decalin and the like; alkylbenzenes (preferably mono- or di-C 1~6 Alkylbenzenes, such as toluene, xylene, and the like), alkyl esters (preferably C 2~5 Alkyl esters, such as ethyl acetate, isobutyl acetate, and the like), and C 3~5 Included are alkyl alcohols (e.g., isopropanol and the like and their isomers). Mixtures of alkyl benzenes and alkanes are particularly useful.
[0067] In addition to the polymer additive, the polymer mixture may also include a wetting agent (surfactant).To improve the adhesion of the sealant to the microcell and provide a more flexible coating process, a wetting agent (e.g., FC surfactants from 3M Company, Zonyl fluorosurfactants from DuPont, fluoroacrylates, fluoromethacrylates, fluoro-substituted long-chain alcohols, perfluoro-substituted long-chain carboxylic acids, and their derivatives, and Silwet silicone surfactants from OSi (Greenwich, Conn.)) may also be included in the composition. Other components including crosslinking agents (e.g. bisazides such as 4,4'-diazidodiphenylmethane and 2,6-di-(4'-azidobenzal)-4-methylcyclohexanone), vulcanizing agents (e.g. 2-benzothiazolyl disulfide and tetramethylthiuram disulfide), multifunctional monomers or oligomers (e.g. hexanediol, diacrylates, trimethylolpropane, triacrylates, divinylbenzene, diallylphthalene), thermal initiators (e.g. dilauroylperoxide, benzoylperoxide), and photoinitiators (e.g. isopropylthioxanthone (ITX), Irgacure 651 and Irgacure 369 from Ciba-Geigy) are also very useful to improve the physico-mechanical properties of the sealing layer by crosslinking or polymerization reactions during or after the overcoating process.
[0068] The microcell array 700 may be prepared by any of the methods described above. As shown in cross section in Figures 7A-7D, the microcell walls 102 extend upward from the backing layer 101 (the bottom of the microcell) and the conductive layer 210 (which may serve as the first light-transmissive electrode layer of the electro-optic device) to form open microcells. In one embodiment, the conductive layer 210 is formed on or in the backing layer 101. Although Figures 7A-7D show the conductive layer 210 to be continuous and extending above the backing layer 101, it is also possible for the conductive layer 210 to be continuous and extending below or within the backing layer 101, or for the conductive layer 210 to be interrupted by the microcell walls 102.
[0069] The microcells are then filled with an electrophoretic medium 225 comprising electrically charged particles in a non-polar fluid to form a plurality of filled microcells. The microcells can be filled using a variety of techniques. In some embodiments, blade coating may be used to fill the microcells to the depth of the microcell walls 102. In other embodiments, inkjet microinjection may be used to fill the microcells. In yet other embodiments, a microneedle array may be used to fill an array of microcells with the electrophoretic medium 225.
[0070] After filling, the microcells are sealed by applying an aqueous sealing composition to form sealed microcells 780 that include sealing layer 230, as shown in Figure 7C. In some embodiments, the sealing process may include exposure to heat, dry heat, or UV radiation. The sealing layer should have good barrier properties to the non-polar fluids of the electrophoretic medium 225.
[0071] In an alternative embodiment, various individual microcells may be filled with a desired mixture using repeated photolithography. This process typically involves coating an array of empty microcells with a layer of positive-acting photoresist, selectively opening a certain number of microcells by imagewise exposing the positive photoresist and then developing the photoresist, filling the opened microcells with the desired mixture, and sealing the filled microcells by a sealing process. These steps may be repeated to create sealed microcells filled with other mixtures. This procedure allows the formation of large sheets of microcells with desired ratios of mixtures or concentrations.
[0072] Sealing of the filled microcells can be accomplished in several ways. One approach involves mixing an aqueous sealing composition with the electrophoretic medium composition. The aqueous sealing composition may be immiscible with the electrophoretic composition and preferably has a specific gravity less than that of the electrophoretic medium composition. The two compositions, the aqueous sealing composition and the electrophoretic medium composition, are thoroughly mixed and immediately coated onto the microcells using a precision coating mechanism, such as a Mayer bar, gravure, doctor blade, slot coating, or slit coating. Excess fluid is scraped off with a wiper blade or similar device. Residual fluid on the top surface of the partition walls of the microcells may be removed using a small amount of a weak solvent or solvent mixture, such as isopropanol, methanol, or an aqueous solution thereof. The aqueous sealing composition then separates from the electrophoretic medium composition and floats on top of the electrophoretic medium liquid composition. Alternatively, after filling the microcell with a mixture of the electrophoretic medium composition and the aqueous sealing composition, a substrate can be laminated on top to control the metering of the mixture of compositions and promote phase separation of the aqueous sealing composition from the electrophoretic medium composition to form a uniform sealing layer. The substrate used can be a functional substrate in the final structure or a sacrificial substrate, such as a release substrate, that can be removed later. The aqueous sealing composition is then cured in situ (i.e., when in contact with the electrophoretic medium composition) to form a sealing layer. Curing of the aqueous sealing composition can be accomplished by UV or other forms of radiation, such as visible light, IR, or electron beam. Alternatively, when a heat or moisture curable aqueous sealing composition is used, heat or moisture can also be used to cure the aqueous sealing composition.
[0073] In another approach, the electrophoretic medium composition can be filled into the microcells first, and then the aqueous sealing composition can be overcoated onto the filled microcells. Overcoating may be accomplished by conventional coating and printing processes, such as blanket coating, inkjet printing, or other printing processes. In this approach, the sealing layer is formed in situ by curing the aqueous sealing composition by solvent evaporation, radiation, heat, moisture, or interfacial reaction. Interfacial polymerization followed by UV curing is beneficial to the sealing process. Intermixing between the electrophoretic medium composition and the sealing overcoating is significantly suppressed by forming a thin barrier layer at the interface by interfacial polymerization. Sealing is then completed by a post-curing step, for example by UV radiation. The degree of intermixing can be further reduced by using an aqueous sealing composition with a specific gravity less than that of the electrophoretic medium composition. Volatile organic solvents may be used to adjust the viscosity and thickness of the sealing overcoating. The rheology of the aqueous sealing composition may be adjusted for optimal sealing and coating properties. If a volatile solvent is used in the overcoating, it is preferably immiscible with the solvent in the electrophoretic medium composition.
[0074] After the microcells are filled and sealed, the sealed array may be laminated with a second electrode layer 250 including a plurality of electrodes. As shown in FIG. 7D, the second electrode layer 250 may be attached onto the sealing layer 230 to form an electro-optical device 790. The second electrode layer 250 may be attached onto the sealing layer 230 using an adhesive (adhesive layer not shown in FIG. 7D). The adhesive may be electrically conductive. The adhesive of the adhesive layer may be a pressure sensitive adhesive, a hot melt adhesive, or a heat, moisture, or radiation curable adhesive. The lamination adhesive may be post cured by radiation, e.g., UV, through the top conductive layer if the top conductive layer is transparent to radiation. In other embodiments, the plurality of electrodes may be directly bonded to the sealed array of microcells.
[0075] In general, the microcells can be any shape and can vary in size and shape. The microcells can be of uniform size and shape in one system. However, it is possible to have microcells of a mixture of shapes and sizes. The openings of the microcells can be circular, square, rectangular, hexagonal, or any other shape. The size of the partition area between the openings can also vary. The dimensions of each of the individual microcells are approximately 1×10 1 ~Approx. 1×10 6 μm 2 , about 1×10 2 ~Approx. 1×10 6 μm 2 , or approximately 1 × 10 3 ~Approx. 1×10 5 μm 2 The range may be:
[0076] The depth of the microcells can range from about 5 to about 200 μm, or from about 10 to about 100 μm. The ratio of openings to total area ranges from about 0.05 to about 0.95, or from about 0.4 to about 0.9.
[0077] Electrophoretic displays typically include a layer of electro-optic material and at least two other layers disposed on opposite sides of the electrophoretic material, one of these two layers being an electrode layer. In most such displays, both layers are electrode layers, and one or both of the electrode layers are patterned to define the pixels of the display. For example, one electrode layer may be patterned into elongated row electrodes and the other into elongated column electrodes extending at right angles to the row electrodes, with the pixels being defined by the intersections of the row and column electrodes. Alternatively, more commonly, one electrode layer has the form of a single continuous electrode, and the other electrode layer is patterned into a matrix of pixel electrodes, each of which defines one pixel of the display. In another type of electrophoretic display intended for use with a stylus, printhead, or similar movable electrode separate from the display, only one of the layers adjacent to the electro-optic material layer includes an electrode, and the layer opposite the electro-optic material layer is typically a protective layer intended to prevent the movable electrode from damaging the electro-optic material layer.
[0078] The manufacture of a three-layer electrophoretic display typically requires at least one lamination operation. For example, some of the aforementioned MIT and E Ink patents and applications describe a process for producing an encapsulated electrophoretic display, in which an encapsulated electrophoretic medium, including capsules in a binder, is coated onto a flexible substrate, including an indium tin oxide (ITO) or similar conductive coating on a plastic film. Separately, a backplane is prepared containing an array of pixel electrodes and conductors in suitable arrangement for connecting the pixel electrodes to driving circuitry. To form the final display, the substrate with the electro-optical material layer is laminated to the backplane using a lamination adhesive.
[0079] The aforementioned U.S. Patent No. 6,982,178 describes a method for assembling solid electro-optic displays that are well suited for mass production. Essentially, this patent describes a so-called "front plane laminate" ("FPL") that includes, in order, a light-transmitting electrode layer, a layer of electro-optic material in electrical contact with the light-transmitting electrode layer, an adhesive layer, and a release sheet. Typically, the light-transmitting electrode layer will be carried on a light-transmitting substrate, which is preferably flexible in the sense that the substrate can be manually wrapped around a 10 inch (254 mm) diameter drum (for example) without permanent deformation. The substrate is typically a polymer film, usually having a thickness in the range of about 1 to about 25 mils (25 to 634 μm), preferably about 2 to about 10 mils (51 to 254 μm). The light-transmitting electrode layer is conveniently a thin metal or metal oxide layer, for example aluminum or ITO, or may be a conductive polymer. Poly(ethylene terephthalate) (PET) films coated with aluminum or ITO are commercially available, for example as "aluminized Mylar" ("Mylar" is a registered trademark) from EI du Pont de Nemours & Company, Wilmington DE, and such commercially available materials can be used with good results in the front plane laminate. Assembly of an electrophoretic display using such a front plane laminate may be performed by removing the release sheet from the front plane laminate and contacting the adhesive layer with the backplane under conditions effective to adhere the adhesive layer to the backplane, thereby securing the adhesive layer, the electro-optic material layer, and the light-transmitting electrode layer to the backplane. This process is well suited for mass production, as front plane laminates are typically mass produced using roll-to-roll coating techniques and can then be cut into pieces of any size required for use with a particular backplane.
[0080] US Patent No. 7,561,324 describes a so-called "two-fold release sheet" that is essentially a simplified version of the front plane laminate of the aforementioned US Patent No. 6,982,178. One form of the two-fold release sheet includes a layer of electro-optic material sandwiched between two adhesive layers, one or both of which are covered with a release sheet. Another form of the two-fold release sheet includes a layer of solid electro-optic material sandwiched between two release sheets. Both forms of the two-fold release film are intended for use in a process generally similar to the process for assembling electrophoretic displays from the front plane laminates already described, but two separate laminations are required, typically a first lamination in which the two-fold release sheet is laminated to a front electrode to form a front subassembly, and then a second lamination in which the front subassembly is laminated to a backplane to form the final display, although the order of these two laminations can be reversed if desired.
[0081] US Patent No. 7,839,564 describes a so-called "inverted front plane laminate" that is a variation of the front plane laminate described in the aforementioned US Patent No. 6,982,178. This inverted front plane laminate can include, in order, at least one of a light-transmissive protective layer and a light-transmissive electrode layer, an adhesive layer, an electro-optic material layer, and a release sheet. This inverted front plane laminate is used to form an electro-optic device having a layer of laminating adhesive between the electro-optic material layer and the light-transmissive electrode layer, and a second, typically thin, layer of adhesive may or may not be present between the electro-optic material layer and the backplane. Such electro-optic displays can combine good resolution with good low temperature performance.
[0082] The electrophoretic display of the present invention may include a piezoelectric material layer that includes a piezoelectric material. Such an electrophoretic display may operate without the need for a power supply. This means that the structure of the electrophoretic display is simplified. The piezoelectric material layer may be located (a) between the electro-optical material layer and the first light-transmitting electrode layer, (b) between the electro-optical material layer and the second electrode layer, or (c) next to and alongside the electro-optical material layer.
[0083] Piezoelectricity is the accumulation of electric charge in a solid material (piezoelectric material) in response to applied mechanical stress. Examples of piezoelectric materials include polyvinylidene fluoride (PVDF), quartz (SiO2), berlinite (AlPO4), gallium orthophosphate (GaPO4), tourmaline, barium titanate (BaTiO3), lead zirconate titanate (PZT), zinc oxide (ZnO), aluminum nitride (AlN), lithium tantalate, lanthanum gallium silicate, sodium potassium tartrate, and any other known piezoelectric material. The piezoelectric material layer may further include an ionic liquid.
[0084] A voltage generated by piezoelectricity can drive pigments in an electrophoretic material layer to change the color or image of the electrophoretic material when viewed from the viewing side of the display. For example, an electro-optic display including a piezoelectric material layer can be bent or stressed to generate a voltage that can be used to move color pigments in the electrophoretic material.
[0085] FIG. 8 shows an example of an electro-optic display including a piezoelectric material layer and a sealing layer according to the present invention. FIG. 8 is a cross-sectional view of an electro-optic display 800 including a piezoelectric material layer 802 capable of driving an electro-optic material layer 260. The electro-optic display includes a first light-transmitting electrode layer 210, an electro-optic material layer 260, a piezoelectric material layer 802, and a second electrode layer 250. The piezoelectric material layer 802 is disposed between the second electrode layer 250 and the electro-optic material layer 260, while the electro-optic material layer 260 is disposed between the first electrode layer 210 and the piezoelectric material layer 802. The electro-optic material layer 260 may include a plurality of microcells (not shown in FIG. 8), each of the plurality of microcells including a bottom, a wall, and an opening, each of the plurality of microcells containing an electrophoretic medium. A sealing layer according to the present invention (not shown in FIG. 8) spans the openings of the plurality of microcells. The sealing layer may be disposed adjacent to the piezoelectric material layer 802. The first light transmissive electrode layer 210 may be in the form of a single continuous electrode (also called a conductive layer) and the second electrode layer 250 may comprise a plurality of pixel electrodes (a matrix of pixel electrodes). The display can be bent by a user to generate a voltage sufficient to operate the display.
[0086] FIG. 9 shows a cross-sectional view of another example of an electro-optic display 900 including a piezoelectric material layer 802 capable of driving an electro-optic material layer 260. The electro-optic material layer includes a first light-transmissive electrode layer 210, a piezoelectric material layer 802, an electro-optic material layer 260, and a second electrode layer 250. The piezoelectric material layer 802 is disposed between the first light-transmissive electrode layer 250 and the electro-optic material layer 260, while the electro-optic material layer 260 is disposed between the second electrode layer 250 and the piezoelectric material layer 802. The electro-optic material layer 260 may include a plurality of microcells (not shown in FIG. 9), each of the plurality of microcells including a bottom, a wall, and an opening, each of the plurality of microcells containing an electrophoretic medium. A sealing layer (not shown in FIG. 8) according to the present invention spans the openings of the plurality of microcells. The sealing layer may be disposed adjacent to the second electrode layer 250. The sealing layer may be disposed adjacent to the piezoelectric material layer 802. The electro-optic display may further include an adhesive layer (not shown in FIG. 9 ), which is disposed between the electro-optic material layer 260 and the second electrode layer 250. In particular, the piezoelectric material layer may be in contact with a sealing layer of the electro-optic material layer 260. The first light-transmissive electrode layer 210 may have the form of a single continuous electrode (also called a conductive layer), and the second electrode layer 250 may include a plurality of pixel electrodes (a matrix of pixel electrodes).
[0087] 10 shows a cross-sectional view of an example of an electro-optic display 1000 including (1) a piezoelectric material layer 802 capable of driving an electro-optic material layer 260, and (2) an encapsulation layer according to the present invention. The electro-optic material layer includes a first light-transmissive electrode layer 210, an electro-optic material layer 260, a piezoelectric material layer 802, and a second electrode layer 250. In this embodiment, the piezoelectric material layer 802 is located between the electro-optic material layer and the second electrode layer 250. The piezoelectric material layer 802 overlaps only a first portion of the electrophoretic material layer 260. The second electrode layer 250 overlaps all of the piezoelectric material layer 802 and a second portion of the electro-optic material layer, and the second portion of the electro-optic material layer does not overlap the piezoelectric material layer 802. A first portion of the electro-optic material layer may include a first plurality of microcells (not shown in FIG. 10) and may have a first electrical resistance, while a second portion of the electro-optic material layer may include a second plurality of microcells (not shown in FIG. 10) and may have a second electrical resistance. As shown in FIG. 10, the first light-transmissive electrode layer 210 is adjacent to the electro-optic material layer 260 and is on an opposite side of the electro-optic material layer 260 to the piezoelectric material layer and the second electrode layer 250.
[0088] Each of the first and second pluralities of microcells includes a bottom, a wall, and an opening, and each of the first and second pluralities of microcells contains an electrophoretic medium. An encapsulation layer (not shown in FIG. 10) according to the present invention spans the openings of the first and second pluralities of microcells. The encapsulation layer may be disposed adjacent to the piezoelectric material layer 802 and the second electrode layer 250 (on the side of the electro-optic material layer opposite the first light-transmissive electrode layer 210).
[0089] In another example, instead of laminating the piezoelectric material layer directly on or over the electro-optic material layer as shown in Figures 8, 9 and 10, the piezoelectric material layer 802 may be laminated on a semiconductive or highly resistive layer 1112, which is then laminated on the first light-transmitting electrode layer 210, as shown in Figure 11. In this configuration, the electro-optic display 1100 includes a semiconductive or highly resistive layer 1112. The semiconductive or highly resistive layer 1112 replaces a portion of the electro-optic material layer 260 above the piezoelectric material layer 802, thereby reducing the overall thickness of the display and preventing fast dissipation of charge across the piezoelectric material layer 802 so that locally generated charge (by the piezoelectric material layer 802) can be effectively and efficiently applied onto the electro-optic material layer 260. This leads to an improvement in the contrast ratio of the display. As shown in FIG. 11, the first light-transmitting electrode layer 210 and the second electrode layer 250 sandwich an electro-optic material layer 260, a semiconducting or highly resistive layer 1112, and a piezoelectric material layer 802. The electro-optic material layer 260 may include a plurality of microcells (not shown in FIG. 11), each of the plurality of microcells including a bottom, a wall, and an opening, each of the plurality of microcells containing an electrophoretic medium. An encapsulation layer (not shown in FIG. 11) according to the present invention spans the openings of the plurality of microcells. The encapsulation layer (not shown in FIG. 11) may be disposed adjacent to the first electrode layer 210. The encapsulation layer (not shown in FIG. 11) may be disposed adjacent to the second electrode layer 250.
[0090] In another example, FIG. 12 shows a cross-sectional view of an electro-optic display 1200 including a piezoelectric layer and an encapsulation layer according to the present invention. The display 1200 differs from the display shown in FIG. 11 in that only a portion of the piezoelectric material layer 802 overlaps with the first light-transmitting electrode layer 210. In this configuration, the piezoelectric material layer 802 can be avoided from being placed in a neutral plane position so that a better image can be generated from the piezoelectric material layer 802. In addition, the piezoelectric material layer 802 can be a metalized piezoelectric material layer and can be covered by a metal layer 1213. In some embodiments, the first semiconducting layer 1112 can be located between the metal layer 1213 and the first electrode light-transmitting layer 210. Another semiconducting layer, the second semiconducting layer 1210, can be located between the piezoelectric material layer 802 and the second electrode layer 250. It should be understood that all layers presented herein, including the first electrode layer 210 and the second electrode layer 250, may be light transmissive so that the display may be viewed from any direction or orientation. The electro-optic material layer 260 may include a plurality of microcells (not shown in FIG. 12), each of the plurality of microcells including a bottom, a wall, and an opening, each of the plurality of microcells containing an electrophoretic medium. An encapsulation layer (not shown in FIG. 12) according to the present invention spans the openings of the plurality of microcells. The encapsulation layer (not shown in FIG. 12) may be disposed adjacent to the second electrode layer 250. The encapsulation layer (not shown in FIG. 12) may be disposed adjacent to the second semiconducting layer 1210.
[0091] FIG. 13 shows a cross-sectional view of yet another example of an electro-optic display 1300. The electro-optic display 1300 includes a piezoelectric material layer and a sealing layer according to the present invention. As shown in FIG. 13, the electro-optic material layer 260 may extend partially under and overlap the piezoelectric material layer 802 to ensure a reliable connection with the piezoelectric material layer 802. In this example, the electro-optic display layer 260 may have a portion with microcells 607 and another portion 1315 that is substantially flat and configured to establish a connection with the piezoelectric material layer 802. In this configuration, the piezoelectric material layer 802 is positioned to overlap the substantially flat portion 1315 to ensure a good connection with the electro-optic material layer 260. This configuration can advantageously establish a strong connection between the piezoelectric material layer 802 and the electro-optic material layer 260. For example, this configuration provides a robust connection between the electro-optic material layer 260 and the piezoelectric material layer 802 that can withstand repeated bending or stress applied to the electro-optic display 1300. In addition, an adhesive layer 240 may be disposed between the piezoelectric material layer 802 and the first optically transparent electrode layer 210. Each of the microcells 607 includes an opening, and the sealing layer 230 spans each microcell opening. Additionally, a second electrode layer 250 is adjacent to the electro-optic material layer 260. The second electrode layer 250 is disposed between the substrate 1316 and the electro-optic material layer 260.
[0092] The sealing layer in the example electro-optic displays illustrated by Figures 8, 9, 10, 11, 12, and 13 is water resistant. The sealing layer comprises 40 to 95 weight percent poly(vinyl alcohol), based on the weight of the sealing layer excluding solvent, where the poly(vinyl alcohol) contains acetoacetate functional groups in its molecular structure; and 5 to 60 weight percent polyurethane, based on the weight of the sealing layer excluding solvent.
[0093] Electrophoretic medium.
[0094] Electrophoretic medium in the context of the present invention refers to the composition within the microcells. For display applications, the microcells may be filled with at least one type of charged pigment particles in a non-polar fluid. The electrophoretic medium may contain one type of charged particle or more than one type of particle with different colors, charges, and charge polarities. The charged particles move through the electrophoretic medium under the influence of an electric field applied across the electro-optical material layer. The charged particles may be inorganic or organic pigments with a polymeric surface treatment to improve their stability. The electrophoretic medium may contain pigments with white, black, cyan, magenta, yellow, blue, green, red, and other colors. The electrophoretic medium may also contain charge control agents, charge adjuvants, rheology modifiers, and other additives. Examples of non-polar fluids include hydrocarbons such as Isopar, decahydronaphthalene (DECALIN), 5-ethylidene-2-norbornene, fatty oils, paraffin oils, silicon fluids, aromatic hydrocarbons such as toluene, xylene, phenylxylylethane, dodecylbenzene, or alkylnaphthalenes, halogenated solvents such as perfluorodecalin, perfluorotoluene, perfluoroxylene, dichlorobenzotrifluoride, 3,4,5-trichlorobenzotrifluoride, chloropentafluoro-benzene, dichlorononane, or pentachlorobenzene, and perfluorinated solvents such as FC-43, FC-70, or FC-5060 from 3M Company (St. Paul MN), low molecular weight halogen-containing polymers such as poly(perfluoropropylene oxide) from TCI America (Portland, Oregon), poly(chlorotrifluoro-ethylene) such as Halocarbon from Halocarbon Product Corp. (River Edge, NJ). Oils, perfluoropolyalkyl ethers such as Galden from Ausimont, or the K-Fluid series of Krytox oils and greases from DuPont (Delaware), polydimethylsiloxane-based silicone oils (DC-200) from Dow-corning.
[0095] The electrophoretic medium may include two or more types of charged particles. The electrophoretic medium may include four types of charged particles, namely a first type, a second type, a third type and a fourth type of charged particles. The first, second, third and fourth types of charged particles may include first, second, third and fourth types of pigments having first, second, third and fourth colors, respectively. The first, second, third and fourth colors may be different from each other. The first type of particles may include an inorganic pigment and have a first charge polarity. The second and third types of particles may have a second charge polarity opposite to the second charge polarity. The fourth type of particles may have the first charge polarity or the second charge polarity. The first type of particles may be white. The second, third and fourth types of charged particles may have a color selected from the group consisting of cyan, magenta and yellow.
[0096] Sealing layer
[0097] The sealing layer must provide a barrier to the electrophoretic medium so that the non-polar fluid is not removed from the plurality of microcells. Furthermore, since the sealing layer contacts the electrophoretic medium and seals it within the microcavities, the sealing layer must be (1) practically insoluble in the non-polar fluid of the electrophoretic medium and (2) a good barrier to the non-polar fluid so that the non-polar fluid does not diffuse out of the microcells during the life of the device. A poor barrier property of the sealing layer to the non-polar fluid leads to loss of fluid from the electrophoretic medium and sagging of the sealing layer. In certain applications, where the electrophoretic device may be subjected to harsh conditions, such as exposure to water or even insertion into water, the sealing layer must also be water resistant. That is, the sealing layer must be resilient in water and must protect the electrophoretic medium under such conditions. The sealing layer must not adversely affect the electro-optical performance of the device.
[0098] The present inventors have discovered that a sealing layer comprising a combination of poly(vinyl alcohol) and polyurethane, where the poly(vinyl alcohol) contains acetoacetate functional groups in its molecular structure, provides such benefits. The poly(vinyl alcohol) used to form the sealing layer may be water soluble.
[0099] An example of a poly(vinyl alcohol) that contains acetoacetate functional groups in its molecular structure is GOHSENX supplied by Mitsubishi Chemical Corporation. TM Z-410. This material is crosslinkable and can be crosslinked by heat treatment or exposure to UV radiation. Other commercially available examples of poly(vinyl alcohol)s that contain acetoacetate functional groups in their molecular structure include GOHSENX TM Z-100, GOHSENX TM Z-200, GOHSENX TM Z-205, GOHSENX TM Z-210, GOHSENX TM Z-220, GOHSENX TM Z-300, and GOHSENX TMZ-320. The poly(vinyl alcohol) can be a copolymer formed by polymerization of vinyl alcohol and vinyl acetoacetate. The poly(vinyl alcohol) can be a terpolymer formed by polymerization of vinyl alcohol, vinyl acetate, and vinyl acetoacetate. The sealing layer comprises 40 weight percent to 95 weight percent poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure, based on the weight of the sealing layer excluding the solvent. The sealing layer may comprise 45 weight percent to 93 weight percent, or 50 weight percent to 90 weight percent, or 55 weight percent to 85 weight percent, or 60 weight percent to 80 weight percent, or 65 weight percent to 78 weight percent poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure, based on the weight of the sealing layer excluding the solvent. The poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure may have a degree of hydrolysis of 90 percent to 99 percent, or 91 percent to 98 percent, or 92 percent to 96 percent. The poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure may have a number average molecular weight of 1,000 to 1,000,000 daltons, or 10,000 to 800,000 daltons, or 20,000 to 700,000 daltons, or 40,000 to 600,000 daltons. The poly(vinyl alcohol) of the sealing layer may be crosslinked. The crosslinked poly(vinyl alcohol) may be formed by reaction of a crosslinking agent with the starting (non-crosslinked) poly(vinyl alcohol). The crosslinking reaction may occur at the hydroxyl groups or the acetoacetate functional groups of the poly(vinyl alcohol). The crosslinking agent reacts with two or more poly(vinyl alcohol) polymer molecules to form a bond between the polymers. The bond may be a covalent bond. The crosslinker may have two or more reactive functional groups, such as an alcohol, an amine, and an aldehyde.Non-limiting representative examples of classes of crosslinkers include diamines, polyamines, diols, polyols, dialdehydes, dihydrazides, organotitanates, organozirconates, and organoborates. The crosslinker can be a saturated dialdehyde having 2-6 carbon atoms, such as glyoxal. Other examples of poly(vinyl alcohol) crosslinkers include methoxydiamine, 1,3-bis(aminomethyl)cyclohexane, adipoyldihydrazide, ZrO(OH)Cl·nH2O, (NH4)2ZrO(CO3)2, Sequarez 755, and Safelink. TM One example is SPM-01.
[0100] A crosslinked poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure can be formed by a crosslinkable poly(vinyl alcohol) and a crosslinking agent. The crosslinking agent has a pot life of greater than 1 day. The crosslinking agent may have a pot life of greater than 2 days, greater than 3 days, greater than 5 days, or greater than 7 days.
[0101] The sealing layer of the present invention comprises 5 weight percent to 60 weight percent polyurethane, based on the weight of the sealing layer excluding the solvent. The sealing layer may comprise 10 weight percent to 55 weight percent, or 15 weight percent to 50 weight percent, or 18 weight percent to 45 weight percent, or 20 weight percent to 40 weight percent, or 22 weight percent to 35 weight percent polyurethane, based on the weight of the sealing layer excluding the solvent. The polyurethane may be an ester polyurethane or a polycarbonate polyurethane. The polyurethane may have a number average molecular weight of 1,000 to 2,000,000 daltons, 5,000 to 1,500,000 daltons, 10,000 to 1,000,000 daltons, or 30,000 to 800,000 daltons. The polyurethane of the sealing layer may be crosslinked. The crosslinked polyurethane may be formed by crosslinking a crosslinkable polyurethane using a crosslinking agent. The crosslinking agent may be a polyisocyanate, a polyfunctional polycarbodiimide, a polyfunctional aziridine, a silane coupling agent, a boron / titanium / zirconium based crosslinking agent, or melamine formaldehyde. The poly(vinyl alcohol) and polyurethane of the same sealing layer may both be crosslinked.
[0102] Polyurethanes are typically prepared by polyaddition processes involving diisocyanates. Non-limiting examples of polyurethanes include polyether polyurethanes, polyester polyurethanes, polycarbonate polyurethanes, polyether polyureas, polyureas, polyester polyureas, polyester polyureas, polyisocyanates (e.g., polyurethanes containing isocyanate bonds), and polycarbodiimides (e.g., polyurethanes containing carbodiimide bonds). Generally, polyurethanes contain urethane groups. The polyurethanes utilized in the aqueous sealing compositions and sealing layers described herein can be prepared using methods known in the art. Preferably, the polyurethanes of the aqueous sealing compositions and sealing layers of the present invention are polyester polyurethanes, polycarbonate polyurethanes, and mixtures thereof.
[0103] The polyurethane of the sealing layer of the present invention can have a high degree of crystallinity as determined by X-ray diffraction (XRD). Typically, polyurethane has a segment structure, i.e., hard segments derived from the isocyanate component (or chain extender, if present) and soft segments derived from the diol (or polyol) component. The nature and molecular structure of the monomers used in polyurethane synthesis play an important role in the properties of the hard and soft segments. Typically, the crystallinity of polyurethane can be controlled by the selection of diol (or polyol) monomers.
[0104] The inventors of the present invention have observed that the use of polyurethanes with specific melting characteristics shows improved water resistance of the corresponding sealing layer. Specifically, polyurethanes with a peak melting temperature (Tm) of 115°C and higher, and a crystallinity index (Ic) of 8% and higher show improved water resistance. The peak melting temperature (Tm) and the crystallinity index (Ic) were measured by differential scanning calorimetry (DSC). The DSC method involves increasing the temperature of a polyurethane sample from 30°C to 220°C at a rate of 10°C. The heat flow is measured at various temperatures. The lowest point on the line of heat flow (in W / g) versus temperature is the peak melting temperature (Tm). The area of the graph (between the baseline and the heat flow line) corresponds to the enthalpy of melting (expressed in J / g). The crystallinity index (Ic) is determined as the ratio of (A1 / A) multiplied by 100, where A is the area between the baseline and the heat flow line. Area A1 is the area that corresponds to the area of the graph below the peak melting temperature, and is defined by the straight line connecting the lowest point of the graph (corresponding to the peak melting temperature) and the point on the baseline that corresponds to the onset temperature.
[0105] The sealing layer may comprise poly(vinyl alcohol) in a weight ratio to polyurethane of 19-0.7, or 15-0.8, or 10-1, or 8-1.5, or 5-2.
[0106] The sealing layer of the present invention may further include a surfactant. The aqueous sealing composition (and the corresponding sealing layer) may also include a wetting agent, also called a surfactant. Examples of wetting agents include FC surfactants from 3M Company, Zonyl fluorosurfactants, fluoroacrylates, fluoromethacrylates, fluoro-substituted long-chain alcohols, perfluoro-substituted long-chain carboxylic acids, and their derivatives from DuPont, and Silwet silicone surfactants from OSi (Greenwich, Conn). The wetting agent can increase the affinity between the sealing layer and the microcell, increase the interfacial area between them, improve the adhesion of the sealing layer to the microcell, and provide a more flexible coating process. The surfactant may be an acetylenic diol. Non-limiting examples of acetylenic diols are 7,10-dimethyl-8-hexadecyne-7,10-diol, 4,7-dimethyl-5-decyne-4,7-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, and 3,6-dimethyl-4-octyne-3,6-diol. Commercially available acetylene diols include DYNOL TM 607, DYNOL TM 604, Surfynol® 104, Surfynol® 465, Surfynol® 440, Surfynol® 485, Surfynol® 2502, and Surfynol® FS-85. TM and Surfynol® surfactants supplied by Evonik. The surfactant can be an organosilicone surface tension reducing agent, such as Silwet® L-7607 supplied by Momentive.
[0107] The sealing layer may be formed by an aqueous sealing composition that may include (i) 40 to 95 weight percent poly(vinyl alcohol), based on the weight of the aqueous sealing composition excluding the solvent, the poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure, and (ii) 5 to 60 weight percent polyurethane, based on the weight of the aqueous sealing composition excluding the solvent, and (iii) an aqueous carrier.
[0108] The aqueous sealing composition may comprise from 5 to 98 weight percent, or from 10 to 90 weight percent, or from 15 to 80 weight percent, or from 20 to 70 weight percent, or from 25 to 60 weight percent of the aqueous carrier, based on the weight of the aqueous sealing composition.
[0109] The application, drying, or curing of the aqueous sealing composition forms a sealing layer, which may have some residual water and other solvents remaining in the sealing layer after drying or curing.
[0110] The polyurethane may be added to the aqueous sealing composition as an aqueous solution, or an aqueous dispersion, or an aqueous emulsion, or a latex.
[0111] The aqueous sealing composition may include 0.5 to 10 weight percent of a polyurethane crosslinker, based on the weight of the aqueous sealing composition excluding the solvent. The polyurethane crosslinker forms a chemical bond between the polyurethane of the aqueous sealing composition and the polymer molecules of the microcell to increase adhesion between the sealing layer and the microcell. The polyurethane crosslinker is preferably soluble or dispersible in the aqueous carrier of the sealing composition. The polyurethane crosslinker can be a monomer, oligomer, or polymer. Examples of polyurethane crosslinkers include polyisocyanates, polyfunctional polycarbodiimides, polyfunctional aziridines, silane coupling agents, boron / titanium / zirconium based crosslinkers, or melamine formaldehyde. The polycarbodiimide crosslinker is reactive at acidic pH conditions. Preferably, the crosslinker does not include a sulfosuccinate surfactant.
[0112] The aqueous sealing composition may contain 0.1 to 10 weight percent of a poly(vinyl alcohol) crosslinker, based on the weight of the aqueous sealing composition excluding the solvent.
[0113] The aqueous sealing composition is prepared by mixing the components in a water carrier. The aqueous sealing composition can be applied to a suitable surface to form a sealing layer. The aqueous sealing composition can be used to form a sealing layer immediately after its preparation or, more typically, several hours or days after its preparation. If the aqueous sealing composition needs to be stored for a period of time before use, care must be taken to obtain an aqueous sealing composition that is stable over time. For example, the aqueous sealing composition must be a fluid with a sufficiently low viscosity so that the aqueous sealing composition can be successfully applied to form a sealing layer. This means that the aqueous sealing composition must have a sufficiently long pot life. In some cases, the poly(vinyl alcohol) crosslinker, if present, may increase the viscosity of the aqueous sealing composition to a level that precludes its use to form a sealing layer. Thus, care must be taken to utilize a poly(vinyl alcohol) crosslinker that results in an aqueous composition with a sufficiently long pot life. The aqueous sealing composition may have a pot life of more than 1 day, more than 3 days, more than 5 days, or more than 7 days. A non-limiting example of a poly(vinyl alcohol) crosslinker that provides a long pot life is Safelink 1000, supplied by Mitsubishi Chemical Corporation. TM SPM-01, glyoxals, and organic zirconates such as ZrO(OH)Cl*nH2O (supplied as ZIRCOZOL ZC-2 by Daiichi Kigenso Kagaku Kogyo Co., Ltd.) and (NH4)2ZrO(CO3)2 (supplied as ZIRCOZOL AC-7 by Daiichi Kigenso Kagaku Kogyo Co., Ltd.).
[0114] The aqueous sealing composition may also include a pH adjuster. The pH adjuster is added to the aqueous sealing composition to adjust its pH to a value of 6.5 to 8.5. One example of a pH adjuster is ammonium hydroxide, but various acids and bases can be used. The pH adjuster increases the pH of the aqueous sealing composition, which can reduce the crosslinking rate of the aqueous sealing composition before use, and provides optimal pH conditions for the rheology modifier to interact with the particles of the aqueous sealing composition, improving its efficacy. The pH adjuster may be used at a content of 0.2 to 1 weight percent based on the weight of the sealing composition excluding the solvent.
[0115] The aqueous sealing composition (and resulting sealing layer) may also include 0.05 to 10 weight percent, or 0.1 to 5 weight percent, or 0.5 to 2 weight percent of a rheology modifier, based on the weight of the aqueous sealing composition (and corresponding sealing layer) excluding the solvent. The rheology modifier increases the stability of the aqueous sealing composition during storage. The rheology modifier also promotes film formation, improves sealing stability, and provides other functions. Examples include associative thickeners, alkali swellable acrylic emulsions, and other polymeric thickeners. The aqueous sealing composition may include hydrophobically modified alkali swellable acrylic emulsions, such as Solthix supplied by Lubrizol, as rheology modifiers. TM The aqueous sealing composition may include A-100. The aqueous sealing composition may be shear thinning, i.e., its viscosity decreases with higher shear. For example, the rheological profile of the aqueous sealing composition may be -4 Viscosity at 1 / s and shear rate 10 2 The viscosity at 1 / s can show a decrease of 1 / 5 to 1 / 10,000 times.
[0116] These and other aspects of the present invention will be further understood through a consideration of the following examples, which are intended to illustrate certain particular embodiments of the invention, but are not intended to limit the scope of the invention as defined by the claims. EXAMPLES
[0117] Methods for evaluating aqueous sealing compositions and sealing layers
[0118] A. An example of the preparation of an aqueous sealing composition for forming a sealing layer.
[0119] Example of preparation of aqueous sealing composition. An aqueous polyurethane dispersion was combined with a surfactant and an aqueous poly(vinyl alcohol) solution in a container. The dispersion was mixed for 10 minutes at 90 rpm using a Hei-torque Value 200 overhead mixer. An appropriate amount of polyurethane crosslinker was then added, an appropriate amount of poly(vinyl alcohol) crosslinker was added, and the dispersion was mixed for an additional 60 minutes at 90 rpm. The pH was then adjusted to 6.5-8.5 using ammonium hydroxide, and the dispersion was mixed for an additional 30 minutes. An appropriate amount of rheology modifier was added dropwise to the dispersion, and mixing was continued for an additional 60 minutes. The dispersion was then degassed under reduced pressure (25 mmHg) for 5 days. The resulting aqueous sealing composition was used for the preparation of a sealing layer of a corresponding display.
[0120] B. Example of preparation of sealing layer using the drawdown method.
[0121] The water-based sealing composition prepared in A above was coated onto the ITO side of an indium tin oxide (ITO)-PET film using a Gradco drawdown coater. A square applicator with a 15 mil gap and 8 passes was used. The drawdown speed was set at 2 m / min and a dry film thickness of 30±2 μm was targeted. The coating was dried in an oven at 100° C. for 15 minutes. The dried film was conditioned at 25° C. and 55% relative humidity (RH) for 24 hours.
[0122] C. Evaluation of the barrier properties of the sealing layer against non-polar fluids.
[0123] The aqueous composition prepared in section A above was used to form the sealing layer of the display 1400 shown in FIG. 14A. The sealing layer was formed by the method described in B above. The display 1400 included, in order, a substrate 1403, a first light-transmissive electrode layer 210 (conductive layer), a primer layer 1405, a microcell layer 220, and a sealing layer 230. The microcell contained an electrophoretic medium comprising pigment particles in Isopar E. The device 1400 was stored at 70° C. for at least 24 hours. After this period, the electro-optic display was inspected using an optical microscope for sagging of the sealing layer caused by loss of non-polar fluid of the electrophoretic medium. If the distance between the bottom of the inspected microcavity and the lowest point of the bottom surface of the sealing layer is less than 85% of the distance between the bottom of the microcavity and the highest point of the lower surface of the sealing layer of the same microcell, the sealing layer is marked as failing its barrier properties. Otherwise, i.e., if the distance between the bottom of the inspected microcell and the lowest point of the sealing layer is 85% or more of the distance between the bottom of the microcell and the highest point of the bottom surface of the sealing layer of the inspected microcell, the sealing layer is marked as passing for its barrier properties. The evaluation of the barrier properties can also be done qualitatively by observing the prepared electro-optical device by optical microscopy looking from the viewing side of the display. A display containing a severely sagging sealing layer has a significantly different appearance (uniform surface vs. non-uniform surface) than a device containing a sealing layer with good barrier properties to non-polar fluids. For example, a microcell with a sealing layer that appears uniform as shown in FIG. 15A and, conversely, a microcell with a sealing that appears non-uniform as shown in FIG. 15B.
[0124] D. Preparation of electro-optic displays.
[0125] An electro-optical device was prepared by filling a mixture of charged pigment particles (white, black, and red) in Isopar E into a plurality of microcells, then coating with an aqueous sealing composition as described in B above. The display shown in FIG. 14B was constructed. The electro-optical display 1450 included, in order, a protective film 1451, an optically clear first adhesive layer 1452, a substrate 1403, a first light-transmissive electrode layer 210 (conductive layer), a primer layer 1405, a microcell layer 220, a sealing layer 230, a second adhesive layer 240, an ITO electrode layer 1455, and a glass layer 1460. A source of electric field 1461 electrically connected the first light-transmissive electrode layer 210 (conductive layer) with the ITO electrode layer 1455. The first light-transmissive layer 210 was approximately 25 μm thick. The substrate 1453 was approximately 100 μm thick. The primary layer 1405 was approximately 0.4 μm thick. The microcell layer 220 contained a plurality of microcells. Each microcell had an approximate bottom thickness of 0.4 μm and an approximate height of 14 μm. The sealing layer 230 was approximately 10 μm thick and the second adhesive layer was approximately 6 μm thick.
[0126] E. Evaluation of water resistance of sealing layer.
[0127] E1. The electro-optic display prepared in D above was switched to its red state and then submerged in a beaker containing water of neutral pH for 2 hours at 25° C. After this time, the display was removed from the beaker and visually inspected.
[0128] E2. The electro-optic display prepared in D above was switched to its red state and then submerged in a beaker containing neutral pH water for 15 minutes at 100° C. After this time, the display was removed from the beaker and visually inspected.
[0129] Determination of Water Resistance of Electro-Optic Displays After removing the electro-optic display from the beaker, the display was visually inspected and rated as pass or fail based on the following criteria: Fail: The sealing layer of the display has delaminated from adjacent layers, the sealing layer contains cracks, or the color of the display has visibly changed from the same display before it was submerged in water. Pass: The display's sealing layer has no areas that have delaminated from adjacent layers, the sealing layer contains no cracks, and the color of the display is not visibly changed from the same display before submersion in water.
[0130] F. Electro-optical performance evaluation methods.
[0131] The electro-optical performance of a display prepared by Method B above was measured by switching it to its white state and measuring the color of the white state using a color computer (Spectrophotometer i1 supplied by x-rite). The display was switched to its red state and measuring the color of the red state using a color computer (Spectrophotometer i1 supplied by x-rite). Results are reported using CIELab color space values (L*, a*, and b*) for each color state (white and red).
[0132] G. Evaluation of peak melting temperature and crystallinity index of polyurethanes by differential scanning calorimetry.
[0133] A known mass of polyurethane was placed in a DSC pan and the pan was sealed with a DSC lid. The sample was heated from 30°C to 220°C at a rate of 10°C using a differential scanning calorimeter TA DSC25 supplied by TA Instruments. A graph of normalized heat flow (in W / g) versus temperature was made. The lowest point P on the graph line is the peak melting temperature. The graph area (A) between the baseline and the normalized heat flow line was determined. Area A corresponds to the enthalpy of melting. A line was drawn from point P on the graph, which corresponds to the peak melting temperature, to point B on the baseline of the onset temperature. This line (PB) separates area A into areas A1 and A2. Area A1 corresponds to the area below the peak melting temperature and area A2 corresponds to the area above the peak melting temperature. The crystallinity index is the ratio of A1 / A multiplied by 100. That is, Ic=100×(A1 / A).
[0134] Evaluation results
[0135] Unless otherwise indicated, the amounts of components in the disclosed compositions are on a dry basis (without solvent). Some compositions use the term QS (quantity sufficient) to describe the content of the carrier. This means that the content of this component in the composition is equal to, and does not exceed, the amount required to achieve a total of 100 percent of the composition.
[0136] Several aqueous sealing compositions were prepared according to the general method described above in A. The compositions prepared are shown in Table 1.
[0137] [Table 1]
[0138] Table 2 shows an overview of the sealing layer compositions, and the sealing layers are formed using the compositions in Table 1. That is, sealing layer composition Comparative Example 1S is formed by the aqueous sealing composition from Comparative Example 1, sealing layer composition Comparative Example 2S is formed by the aqueous sealing composition from Comparative Example 2, sealing layer composition Example 3S is formed by the aqueous sealing composition from Example 3 (invention), and sealing layer composition Example 4S is formed by the aqueous sealing composition from Example 4 (invention). The content is the weight percent of the component based on the weight of the composition excluding the water carrier (and other residual solvents). That is, sealing layer composition Comparative Example 1S is formed by the aqueous sealing composition from Comparative Example 1, sealing layer composition Comparative Example 2S is formed by the aqueous sealing composition from Comparative Example 2, sealing layer composition Example 3S is formed by the aqueous sealing composition from Example 3 (invention), sealing layer composition Example 4S is formed by the aqueous sealing composition from Example 4 (invention), and sealing layer composition Example 5S is formed by the aqueous sealing composition from Example 5 (invention). The physical properties of the polyurethanes of the examples were determined by the method described in Method G above.
[0139] [Table 2]
[0140] Information on the materials of the compositions shown in Tables 1 and 2: [1] GOHSENX supplied by Mitsubishi Chemical Corporation TM Z-410; degree of hydrolysis 98 percent; [2] Poly(vinyl alcohol-co-ethylene) copolymer; Exceval supplied by Kuraray TM RS-1717; degree of hydrolysis 93 percent; ethylene content 8 percent; [3] Polyurethane aqueous dispersion; HD2125 aqueous dispersion supplied as a 35% dispersion in water by Hauthaway; [4] Polyurethane aqueous dispersion (polyester); Witcobond® 386-03 supplied by Chemtura Corp; [5] Picassian® XL-701 supplied by Stahl; [6] DYNOL supplied by Evonik TM 604;[7] Solthix supplied by Lubrizol TM A-100.
[0141] Table 3 shows the results of evaluation of electro-optic devices containing encapsulating layers of the compositions shown in Table 2. Electro-optic displays are prepared according to Method D above.
[0142] [Table 3]
[0143] The evaluation results shown in Table 3 were obtained for a sealing layer comprising a combination of poly(vinyl alcohol) and polyurethane, where the poly(vinyl alcohol) contains acetoacetate functional groups (e.g., GOHSENX). TM The sealing layer (Examples S3, S4, and S5) was made of poly(vinyl alcohol) without acetoacetate functionality (e.g., Exceval TM It has been demonstrated that the sealing layer containing the encapsulating layer (RS-1717) exhibits better barrier properties against non-polar fluids and better water resistance at 25° C. than the sealing layers containing the encapsulating layer (Comparative Examples S1 and S2).
[0144] A sealing layer comprising a combination of poly(vinyl alcohol) and polyurethane, wherein the poly(vinyl alcohol) contains acetoacetate functional groups (e.g., GOHSENX). TM Z-410), and the polyurethane has a peak melting temperature of 115° C. and higher, and a crystallinity index of 8% and higher (e.g., HD2125). A sealing layer containing a combination of poly(vinyl alcohol) and polyurethane, where the poly(vinyl alcohol) contains acetoacetate functional groups (e.g., GOHSENX). TM Z-410), which exhibits better water resistance at 100° C. than a sealing layer in which the polyurethane has a peak melting temperature lower than 115° C. and a crystallinity index lower than 8% (e.g., Witcobond® 386-03) (Examples S2 and S3 vs. Example S5).
[0145] Table 4 summarizes the electro-optic performance evaluation results for electro-optic displays including encapsulating layers corresponding to Comparative Example 2S and Example 3S (invention). The data represents the white and red state color data for the corresponding electro-optic displays, as determined by Method F above.
[0146] [Table 4]
[0147] The data in Table 4 show that the color state of electro-optic displays containing sealing layers having the compositions of Comparative Example 2S and Example 3S (invention) is very similar, i.e., the use of the sealing layer composition of the invention does not adversely affect the color state of the display.
Claims
1. A water-resistant sealing layer, a. 40 to 95 weight percent poly(vinyl alcohol), based on the weight of the sealing layer excluding solvent, the poly(vinyl alcohol) containing acetoacetate functional groups in its molecular structure; and b. 5 to 60 weight percent polyurethane, based on the weight of the sealing layer excluding solvent. A water-resistant sealing layer comprising:
2. 10. The water-resistant sealing layer of claim 1, wherein the polyurethane has a peak melting temperature of 115°C and higher, and a crystallinity index of 8% and higher.
3. The water-resistant sealing layer of claim 1 , wherein the polyurethane is crosslinked.
4. 4. The water-resistant sealing layer of claim 3, wherein the polyurethane is crosslinked by a crosslinking agent, the crosslinking agent being a polyisocyanate, a multifunctional polycarbodiimide, a multifunctional aziridine, a silane coupling agent, a boron / titanium / zirconium based crosslinking agent, or melamine formaldehyde.
5. The water-resistant sealing layer of claim 1 , wherein the poly(vinyl alcohol) is crosslinked.
6. 6. The water-resistant sealing layer of claim 5, wherein the crosslinked poly(vinyl alcohol) is formed by reaction of poly(vinyl alcohol) with a crosslinking agent, the crosslinking agent being selected from the group consisting of dialdehydes and organozirconates.
7. The crosslinking agent is glyoxal, ZrO(OH)Cl*nH 2 O, and (NH 4 ) 2 ZrO(CO 3 ) 2 The water-resistant sealing layer of claim 6 selected from the group consisting of:
8. 10. The water-resistant sealing layer of claim 1, wherein the sealing layer further comprises a surfactant, the surfactant being selected from the group consisting of acetylenic diols, organosilicones, and combinations thereof.
9. The water-resistant sealing layer of claim 1 , wherein the sealing layer is formed from a water-based sealing composition.
10. 10. The water-resistant sealing layer of claim 9, wherein the aqueous sealing composition has a pot life of greater than 1 day.
11. The water-resistant sealing layer of claim 9 , wherein the aqueous sealing composition comprises a polyurethane dispersion.
12. The water-resistant sealing layer of claim 9, wherein the polyurethane has a number average molecular weight of 1,000 to 2,000,000 Daltons.
13. 10. The water-resistant sealing layer of claim 9, wherein the poly(vinyl alcohol) has a number average molecular weight of 1,000 to 1,000,000 Daltons.
14. 10. The water-resistant sealing layer of claim 9, wherein the poly(vinyl alcohol) has a degree of hydrolysis of 90 to 99 percent.
15. 1. An electrophoretic display comprising: a first light transmissive electrode layer; 11. An electro-optic material layer comprising the sealing layer of claim 1 and a microcell layer comprising a plurality of microcells, each of the plurality of microcells comprising a bottom, a wall, and an opening, each of the plurality of microcells containing an electrophoretic medium, the electrophoretic medium comprising at least one type of electrically charged pigment particles dispersed in a non-polar fluid, the sealing layer spanning the openings of the plurality of microcells; Second Electrode Layer in turn, an electrophoretic display.
16. 16. The electrophoretic display of claim 15, wherein the polyurethane has a peak melting temperature of 115° C. or higher, and a crystallinity index of 8% or higher.
17. 16. An electrophoretic display as claimed in claim 15, wherein the sealing layer is disposed between the microcell layer and the second electrode layer.
18. 16. The electrophoretic display of claim 15, wherein the electrophoretic medium comprises four types of charged pigment particles, the colors of the four or more types of pigment particles being selected from the group consisting of white, magenta, yellow, cyan, blue, red, green, and black.
19. 16. An electrophoretic display as claimed in claim 15, further comprising a piezoelectric material layer comprising a piezoelectric material, the piezoelectric material layer being disposed between the first light-transmissive electrode layer material and the electro-optical material layer, or between the electro-optical material layer and the second electrode layer.
20. 16. The electrophoretic display of claim 15, wherein the electrophoretic display is used as an authentication element on an object, the object being selected from the group consisting of currency, stock certificates, bonds, negotiable instruments, debit cards, credit cards, documents, and smart cards.
Citation Information
Patent Citations
Method of producing display medium, display medium and display device
JP2012058717A
Aqueous composition, optical film containing the same, polarizing plate and liquid crystal display device using the same.
JP2014534988A
Compositions and methods for sealing microcells
JP2016535293A
Polyhydroxy compositions for sealing electrophoretic displays - Patent Application 20070122999
JP2019510994A
Electrophoretic displays with improved high temperature performance
US20040120024A1